2014
DOI: 10.3109/02656736.2014.915992
|View full text |Cite
|
Sign up to set email alerts
|

Interstitial ultrasound ablation of vertebral and paraspinal tumours: Parametric and patient-specific simulations

Abstract: Purpose Theoretical parametric and patient-specific models are applied to assess the feasibility of interstitial ultrasound ablation of tumours in and near the spine and to identify potential treatment delivery strategies. Methods 3D patient-specific finite element models (n=11) of interstitial ultrasound ablation of tumours associated with spine were generated. Gaseous nerve insulation and various applicator configurations, frequencies (3 and 7 MHz), placement trajectories, and tumour locations were simulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 23 publications
(12 citation statements)
references
References 86 publications
(106 reference statements)
0
12
0
Order By: Relevance
“…Additionally, a parametric patient-specific modeling of interstitial FUS ablation of vertebral tumors using a percutaneous 7 MHz ultrasound device [25] showed that tumors positioned at least 5 mm from the sensitive neural elements could be safely treated. When targeting the MB nerve using an extracorporeal FUS system, the cortical bone of the vertebral body and the transverse and superior articular processes are likely to serve as natural absorbers of ultrasound energy, preventing a significant portion of the far-field ultrasound beam from reaching the critical neural structures.…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, a parametric patient-specific modeling of interstitial FUS ablation of vertebral tumors using a percutaneous 7 MHz ultrasound device [25] showed that tumors positioned at least 5 mm from the sensitive neural elements could be safely treated. When targeting the MB nerve using an extracorporeal FUS system, the cortical bone of the vertebral body and the transverse and superior articular processes are likely to serve as natural absorbers of ultrasound energy, preventing a significant portion of the far-field ultrasound beam from reaching the critical neural structures.…”
Section: Discussionmentioning
confidence: 99%
“…Computer simulations have increasingly been utilized in recent years as assistive tools for thermal treatments and are used as aid for planning, evaluating and optimizing therapies, and to minimize treatment risks preoperatively (20, 23, 28, 29, 32, 33, 37, 117120). To obtain realistic models of thermal therapies it is important to use adequate mathematical functions to model the temperature dependence of tissue properties, or resort to using interpolation based on tabulated data if necessary.…”
Section: Modelling Of Temperature Dependence Of Tissue Propertiesmentioning
confidence: 99%
“…Expansion of indications for FUS inclusive of spinal treatments whether invasive [56] or non-invasive will significantly expand the number of patients 25 that may benefit from this treatment modality. Finally, additional randomized studies for malignant lesions using multimodality approaches including FUS are warranted.…”
Section: Future Directionsmentioning
confidence: 99%